Proceedings of the 4th International Conference on 3D Body Scanning Technologies, Long Beach CA, USA, 19-20 November 2013 2013
DOI: 10.15221/13.127
|View full text |Cite
|
Sign up to set email alerts
|

ShapeMate: A virtual Tape Measure

Abstract: We introduce ShapeMate, a framework for human body shape estimation and classification for on-line fashion applications. Given a single image of a subject our framework is able to simultaneously estimate detailed 3D human body shape and compute foreground segmentation with minimal user input. Once the body shape has been estimated, various semantic parameters are extracted for garment size and style recommendation. Preliminary results demonstrate that a single image holds enough information for accurate shape … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…Related work on human body measurements and body type estimation usually focuses on analyzing the RGB image from which they estimate basic parameters such as body height, hip and waist height [50], or even general body shape divided into several categories like triangle, inverted triangle, rectangle, hourglass, or diamond [51]. Instead of analyzing the RGB image, we chose to use the directly detected skeleton, from which we can calculate the head height, hip height, and shoulder height.…”
Section: B Model Adaptation To the Usermentioning
confidence: 99%
“…Related work on human body measurements and body type estimation usually focuses on analyzing the RGB image from which they estimate basic parameters such as body height, hip and waist height [50], or even general body shape divided into several categories like triangle, inverted triangle, rectangle, hourglass, or diamond [51]. Instead of analyzing the RGB image, we chose to use the directly detected skeleton, from which we can calculate the head height, hip height, and shoulder height.…”
Section: B Model Adaptation To the Usermentioning
confidence: 99%
“…There is currently a variety of work that provides size recommendation. Some tools focus on electronically measuring a user's body shape from users' pictures ( [7], [10]), while others suggest a user's body measurement by using a multiple linear regression approach and a neural network approach when given information on a user's stature, weight, span, and age [5]. However, in a study, authors have found that most of the users who received the correct size recommendation would not buy the size recommended due to fit preferences [14].…”
Section: Related Workmentioning
confidence: 99%
“…s.t. Constraint (6) The objective function (7) minimizes the weighted pairwise squared difference between normalized sizes across all size types such that the location of the next size must be greater than 0.1 than the previous size in the same size type for all the size types. Constraints (8) specify that all sizes must be greater than 0.…”
Section: Quadratic Program (Qp)mentioning
confidence: 99%